WANPRESTASI DALAM PERJANJIAN YANG BERBASIS APLIKASI DIGITAL - Hanun, Yunan (Jurnal HUKUM BISNIS, 2025)
The development of digital technology has changed the pattern of agreements from conventional models to application-based systems. This transformation brings efficiency in transactions, but at the same time raises legal challenges, especially when default occurs. The problem of default in digital agreements can be in the form of late payments, inappropriate delivery of goods, adverse application technical disturbances, or neglect of obligations by service providers and consumers. These conditions raise questions about how legal protection for the parties and effective dispute resolution mechanisms in the digital realm. This research aims to examine the forms of default and examine the legal remedies available in digital application-based agreements. The method used is normative legal research with a statutory approach and a case approach. Keywords: Agreement, Default, Digital Application